Issues on takaful affecting the choice of accounting policies: a case study of two takaful companies in Malaysia - Annuar, Hairul Azlan; Abu Bakar, Nur Barizah (Canadian Center of Science and Education, 2010)
The paper adopts a descriptive case study method to examine the impact of juristic views on the operations of two Malaysian takaful companies. In order to achieve this objective, the annual financial reports of both companies were analysed. Interviews with each company’s finance managers and with a member of the Malaysian Shariah Advisory Council were undertaken for a more in-depth coverage. Also a written correspondence with a senior official of the central bank was accomplished. Similarities and differences between the two companies were identified and it is concluded that the differences are serious enough to warrant interventions from the regulators in the form of mandatory disclosures in the annual reports.